Assessment of mould growth for library buildings in tropical climates - Ngah Abdul Wahab, S. (EDP Sciences, 2014)
This paper attempt to give a brief insight into the importance of studying mould growth in library building that relates to human health and causes of material deterioration to library materials. It's significant to conduct this research because no similar study has carried out for a library building in Malaysia. Recent literature on the topics reviews to gain insight into developing a theoretical framework and research method. Likewise, the study also supports through pilot study questionnaires with 30 respondents from two different university libraries. The finding revealed to further investigation and mould growth assessment to be conducted that useful in protecting library materials and users health effects through environmental control. Â© Owned by the authors, published by EDP Sciences, 2014.